2016
DOI: 10.1177/2050640615580888
|View full text |Cite
|
Sign up to set email alerts
|

Visceral pain perception in patients with irritable bowel syndrome and healthy volunteers is affected by the MRI scanner environment

Abstract: Background: The MRI scanner environment induces marked psychological effects, but specific effects on pain perception and processing are unknown and relevant to all brain imaging studies. Objectives and methods: We performed visceral and somatic quantitative sensory and pain testing and studied endogenous pain modulation by heterotopic stimulation outside and inside the functional MRI scanner in 11 healthy controls and 13 patients with irritable bowel syndrome. Results: Rectal pain intensity (VAS 0-100) during… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 70 publications
1
8
2
Order By: Relevance
“…Visceral hypersensitivity to liquid ingestion can be the result of alterations in peripheral afferents, spinal cord transmission, exaggerated gastrocolonic reflex, altered central processing of afferent input and/or decreased descending inhibitory input. Other researchers have found reduced CPM efficiency in IBS‐D patients compared to HCs . However, we did not find this reduction.…”
Section: Discussioncontrasting
confidence: 99%
“…Visceral hypersensitivity to liquid ingestion can be the result of alterations in peripheral afferents, spinal cord transmission, exaggerated gastrocolonic reflex, altered central processing of afferent input and/or decreased descending inhibitory input. Other researchers have found reduced CPM efficiency in IBS‐D patients compared to HCs . However, we did not find this reduction.…”
Section: Discussioncontrasting
confidence: 99%
“…In this meta‐analysis, we excluded subgroups with concomitant pain conditions or psychological factors that may influence conditioned pain modulation; in Heymen et al, we excluded patients with migraine and temporomandibular joint disorders . We also excluded conditioned pain modulation measured inside the MRI machine in Wong et al Wilder‐Smith et al [2014] used two conditioned pain modulation paradigms; foot heat and capsaicin as test stimuli . However, enough data to calculate an effect size were only provided for capsaicin as test stimulus and foot heat stimulation as conditioning stimulus, and thus, only this paradigm was used in this meta‐analysis …”
Section: Methodsmentioning
confidence: 99%
“…[10][11][12][13][15][16][17][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40] The baseline characteristics of included studies are shown in Table 1 22,29 Sphere score in 1 study, 24 and the Beck Anxiety Inventory (BAI) in 1 study. 30 …”
Section: Baseline Characteristics Of Included Studiesmentioning
confidence: 99%
“…1,4,9 Animal studies have demonstrated the influence of stress on colonic permeability, and mucosal and systemic inflammation's mediation by the autonomic nervous system and the hypothalamo-pituitary-adrenal axis. 4 Several recently published studies have mapped IBS's relationship with psychological disorders [10][11][12][13][14][15][16] and compared depression and anxiety levels in IBS-subtypes. 15,17,18 However, the relationship between IBS and psychological disorders (depression or anxiety) was inconsistent, even in a recent meta-analysis entailing eight studies.…”
Section: Introductionmentioning
confidence: 99%